(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Back ground Anemia is known to be a ‘silent killer’. Worldwide the prevalence of anemia among the pre-school age group of 6 months to 5 years is 293 million out of these, 89 million children are from India. The NFHS-4 survey revealed that at least 59 % of children between 6 months to 5 years were anemic. The prevalence rates of mild, moderate and severe anemia were 28%, 29% and 2% respectively. The present study was undertaken with an aim to perform a clinico-etiological assessment in children presenting with severe anemia to a tertiary care center. Methods An observational study was conducted at a tertiary health care center. Children with severe anemia satisfying the eligibility criteria with Hb less than 7 g/dl in the age group of 6 months to 60 months as per WHO recommendation were included. Physical examination including anthropometric and systemic examination were performed. An etiological assessment was performed and patients were grouped according to the cause of anemia. Results Out of 1000 patients, 57 patients had severe anemia (5.7%) with 32% of children with heamoglobin levels of <5g/dl. The male to female ratio was 1.5:1. The median age of the children was 22 months. Lower socio-economic status, incomplete immunisation, maternal anemia and malnutrition were observed in patients with severe anemia. The mean hemoglobin was 5.5 g/dl and lowest recorded Hb was 2.6 g/dl. Specific investigations were performed to evaluate for the cause of severe anemia.Nutritional deficiency anemia was the most common cause (82.5%). The other causes of severe anemia were thalassemia (5.35%), infections (5.35%), leukemia (3.5%), other malignancies (1.8%) and aplastic anemia (1.8%). Conclusion The prevalence of severe anemia was 5.7%. Anemia is frequently missed for early diagnosis and they present with symptoms only when there is significantly less hemoglobin levels. Apart from most common cause as nutritional deficiency other serious etiologies also contribute to occurrence of severe anaemia. Early detection and management may result in better outcome.